Techno-economic investigation of a hybrid biomass renewable energy system to achieve the goals of SDG-17 in deprived areas of Iran - Tehrani Mojan Maleki; Akhtari Mohammadreza; Kasaeian Alibakhsh; Rad Mohammad Amin Vaziri; Toopshekan Ashkan; Motlagh Maryam Sadeghi (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Improving the quality of life in deprived areas is one of the main programs of the United Nations, highlighting the significance of a clean and reliable power supply for sustainable development. This study focuses on the configuration of hybrid renewable energy systems (HRES) in Iran's northern and southern rural areas, utilizing a combination of wind turbines, storage banks, photovoltaic panels, biogas, and diesel generators. These regions possess animal-and agriculture-based biomass resources that can effectively meet their primary residential energy needs. This study highlights the importance of employing multi-criteria decision-making (MCDM) for selecting suitable hybrid renewable energy systems (HRES) in rural areas. By incorporating a novel objective weighting process based on the SDG-17 framework, the study considers a range of criteria, including economic, environmental, energy security, and technical factors. Furthermore, the validation of HOMER's accuracy in sizing renewable energy systems with particle swarm optimization (PSO) has demonstrated the significant capability of the primary model. The results demonstrate that relying solely on economically optimal scenarios may not align with CO2 emissions, energy efficiency, and reliability goals. Utilizing the HOMER-MCDM method, the study achieves a more optimal combination of energy systems, considering multiple aspects of sustainable development beyond economic efficiency. For the climates of northern and southern rural regions of Iran, the study identifies the PV/WT/Bio/battery system as the best solution, with levelized costs of electricity (COE) of 0.251 and 0.219 $/kWh, respectively. This configuration relies entirely on local resources, emits nearly zero emissions, and provides power to the communities. Additionally, a sensitivity analysis assesses the impact of changes in capital costs of power generation components and the potential of renewable resources. Adjusting the investment costs of PV and WT systems between 0.7 and 1.3 times their original values results in a COE range of 0.198 to 0.233 $/kWh, representing a decrease of 9.2% and an increase of 6.9% compared to the initial oper-ation, respectively.